(untitled) (Bangladesh Journal of Botany, 2024)
Seven germplasm of Hibiscus cannabinus L. (Acc. No. 95, 4652, 4654, 4655, 4656, 4657, and 4810) were investigated for their karyotype analysis and chromosomal characterization. These germplasm of H. cannabinus were found to possess 2n = 36 chromosomes. Symmetric nature of karyotype was observed in Acc. No. 4654. In contrast, metacentric and submetacentric chromosomes were present in other six accessions revealing the asymmetric nature of karyotype. Based on karyotypic features Acc. No. 4654 was considered relatively primitive and Acc. No. 4652 was relatively advanced among the seven germplasm. Moreover, karyomorphological study proved their divergence in relation to different morphological feature of the chromosomes. Bangladesh J. Bot. 53(4): 967-971, 2024 (December)